2017
DOI: 10.25125/agriculture-journal-ijoear-oct-2017-22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Media on Micropropagation and Rooting of Myrtle (Myrtus communis L.) in In Vitro Conditions

Abstract: Myrtle (Myrtus communis L.) is a small tree shrub of the family Myrtace, grown naturally of the Mediterranean area. Myrtle is very important as an antiseptic, anti-inflammatory and hypoglycemic agent. Turkey has great genetic resources for myrtle. Propagation of myrtle genotypes is significant issue. Plant tissue culture techniques offer fast and reliable micropropagation for many plant species. Different media content could be used for micropropagation in in vitro condition. The aim of the present study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There were some differences in the propagation and rooting parameters of the present genotypes. Previous tissue culture studies in myrtle plants also revealed different outcomes for myrtle genotypes in the same media ( Şimşek et al, 2017 ; Aka Kaçar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…There were some differences in the propagation and rooting parameters of the present genotypes. Previous tissue culture studies in myrtle plants also revealed different outcomes for myrtle genotypes in the same media ( Şimşek et al, 2017 ; Aka Kaçar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…The pH was adjusted to 5.7 by adding 30 g/l sucrose and 6.5 g/l agar to the medium. The medium was poured into culture vessels and sterilized in an autoclave at 121 °C and 1.05 atmosphere pressure (Simsek et al, 2017). Nodal explants were cultured in sterile nutrient medium.…”
Section: Nutrient Mediummentioning
confidence: 99%
“…Its leaves and fruit are rich in phenol and flavonoids. Its phytochemicals and high antioxidant capacity make myrtle plant more important day by day (Şimşek et al, 2017;Hennia et al, 2018;Aka Kaçar et al, 2020). In this study, the 'C-1' genotype with white fruits and the 'C-2' genotype with black fruits were used.…”
Section: Introductionmentioning
confidence: 99%